IMPLEMENTASI KEBIJAKAN TENTANG PENERBITAN SURAT PERSETUJUAN BERLAYAR (SPB) (Studi pada Kantor Kesyahbandaran dan Otoritas Pelabuhan Kelas IV Lhokseumawe) - Taufik Gunawan; Rudi Kurniawan; Muhaddis Muhaddis (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
The purpose of this study is to describe the Implementation of Policies and obstacles in issuing Sailing Approval Letters (SPB) to shipping companies at Class IV Lhokseumawe Port Authority and Harbor Authority Offices. This study uses a qualitative research method that is descriptive by using techniques to obtain data through observation, interviews, and documentation. This study used 10 informants who were determined purposively consisting of the Head of Class IV Lhokseumawe Port Authority and Harbormaster Office along with their staff and several agents from shipping companies. Sailing Approval Letter (SPB) is a State document issued by Syahbandar to every ship that will sail. The results of the study show that the Implementation of the Policy for Issuing Sailing Permits (SPB) at the Class IV Lhokseumawe Port Authority and Harbormaster Office is in accordance with applicable regulations, but there are still several obstacles in its implementation. SPB making services are completed in approximately 3 hours after the complete requirements are received, if the application is incomplete it will be rejected. Obstacles and efforts in Issuing Sailing Approval Letters (SPB) at Class IV Lhokseumawe Port Authority and Harbor Authority Offices include: The applicant's lack of understanding of the procedure for Issuing Sailing Approval Letters (SPB) and Service Procedures for Issuing Sailing Approval Letters (SPB) are still manual and there are limited officers at In the field, the efforts made are to continue to disseminate information to service users.